Degradation of plant peroxisomes by autophagy - Lee, Han Nim; Kim, Jimi; Chung, Taijoon (Frontiers in Plant Science, 2014)
Peroxisomes play a critical role in many metabolic pathways during the plant life cycle. It has been proposed that the transition between different types of peroxisomes involves the degradation of obsolete peroxisomal enzymes via proteolytic activities in the peroxisome matrix, the cytosol, or the vacuole. Forward and reverse genetic studies recently provided evidence for autophagic degradation of peroxisomes in the vacuole of Arabidopsis seedlings. Here, we briefly review a model of pexophagy, or selective autophagy of peroxisomes, in plant cells.